The Potential Role of Protein Kinase R as a Regulator of Age-Related Neurodegeneration - Martinez, Nicolás W.; Gómez, Felipe E.; Matus, Soledad (Frontiers in Aging Neuroscience, 2021)
There is a growing evidence describing a decline in adaptive homeostasis in aging-related diseases affecting the central nervous system (CNS), many of which are characterized by the appearance of non-native protein aggregates. One signaling pathway that allows cell adaptation is the integrated stress response (ISR), which senses stress stimuli through four kinases. ISR activation promotes translational arrest through the phosphorylation of the eukaryotic translation initiation factor 2 alpha (eIF2α) and the induction of a gene expression program to restore cellular homeostasis. However, depending on the stimulus, ISR can also induce cell death. One of the ISR sensors is the double-stranded RNA-dependent protein kinase [protein kinase R (PKR)], initially described as a viral infection sensor, and now a growing evidence supports a role for PKR on CNS physiology. PKR has been largely involved in the Alzheimer’s disease (AD) pathological process. Here, we reviewed the antecedents supporting the role of PKR on the efficiency of synaptic transmission and cognition. Then, we review PKR’s contribution to AD and discuss the possible participation of PKR as a player in the neurodegenerative process involved in aging-related pathologies affecting the CNS.